DIFFERENT ASPECTS OF THE CRIME OF VIOLATION OF THE LEGISLATION ON PERSONAL DATA (ARTICLE 141'2) FROM THE CRIMES PROVIDED FOR IN ARTICLES 141'1, 141'3, 143 OF THE CRIMINAL CODE OF THE REPUBLIC OF UZBEKISTAN. OBJECTIVE AND SUBJECTIVE SIGNS - Isroilov Shaxzod Isomiddin ugli; Khudaykulov Feruzbek Khurramovich (Scholar Express Journals, 2023)
This article examines the different aspects and objective aspects of crimes related to personal information, disclosure of information that undermines a person's dignity and value, violation of the order in which he or she is kept secret to telephone conversations and emails
Keywords: Personal information; personal secret; secret of telephone conversation and correspondence